Young adults’ images of abstaining and drinking: prototype dimensions, correlates and assessment methods - Zimmermann, Friederike; Sieverding, Monika (Journal of health psychology, 2011)
This research investigated contents of actor and abstainer prototypes with regard to young adults? social drinking combining quantitative and qualitative approaches (adjective ratings, N = 300; open answers, N = 90). Exploratory and confirmatory factor analyses yielded two factors (sociability/hedonism, responsibility) in both prototypes, confirmed by qualitative data. Given the importance for intention and willingness to drink alcohol, interventions should focus on the factor ?sociability/hedonism? of the actor and the abstainer prototype to reduce heavy drinking; addressing ?responsibility? may be ineffective. Participants? evaluations appeared to be less prone to mean tendencies subsequent to open answers compared with adjective scales.
First published online October 7, 2010
Gesehen am 19.01.2023